Immigration Policies and the Creation of an Ethnically Segmented Working Class in British Columbia, 1880-1923 - Creese, Gillian (Alternate Routes: A Journal of Critical Social Research, 1984)
This paper examines the role of Canadian immigration policies in the creation of an ethnically segmented working class in pre-Second World War British Columbia. Existing research on the British Columbian working class has documented the radical nature of (white) working class trade union and socialist organization, while at the same time identifying anti-Asian racism as a major feature of organized (white) working class activity in the province. The formation of an ethnically segmented working class occurred through a complex and reciprocal process of ethnic segmentation within the labour market and the political and ideological practices of the working class. In British Columbia, I argue, state immigration policies played a crucial role in this process by according Asian immigrants, in contrast to European and American immigrants, an inferior political status as "non-settlers' within Canada, reinforcing their marginal economic position within the labour market and placing Asian workers in a position of economic and political inferiority vis-a-vis other workers in the province. In this context, immigration policies became a focus of class conflict in British Columbia, and working class organization and consciousness developed in an ethnically segmented and racist form.